OPTIMISING LOCOMOTOR BASIC MOTION LEARNING OUTCOMES THROUGH THE "MOTION CIRCUIT" PLAYING MODEL FOR GRADE 3 STUDENTS - Waluyo; Nugroho, Djoko; Putro, Baskoro Nugroho; Syaifullah, Rony; Mukholid, Agus; Sabarini, Sri Santoso; Liskustyawati, Hanik (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Developing basic locomotor skills is crucial for elementary students, yet conventional teaching methods at SDN 1 Boyolali have led to low engagement and suboptimal outcomes. This study explores the "Motion Circuit" play-based model as a solution, using fun and interactive activities to create a more engaging learning environment for locomotor skills. Through Classroom Action Research (CAR), the model is applied in planning, action, observation, and reflection cycles, allowing for real-time assessment and refinement of teaching strategies. CAR’s structured, collaborative approach supports skill acquisition and effective learning, which the "Motion Circuit" model aims to achieve at SDN 1 Boyolali. Over two research cycles, results showed a significant increase in competencies across affective, cognitive, and psychomotor domains, with outcomes of 100% affective, 82.86% cognitive, and 97.14% psychomotor benchmarks achieved by Cycle II. This engaging model proved highly effective for improving student motivation, comprehension, and physical skills, making it a valuable alternative to traditional Physical Education methods by promoting skill acquisition and a positive learning attitude.